Surgical and Immunohistochemical Outcomes of Scleral Reconstruction with Autogenic, Allogenic and Xenogenic Grafts: An Experimental Rabbit Model. (1st December 2020) - Dereli Can, Gamze; Akcan, Gülben; Can, Mehmet Erol; Akdere, Özge Ekin; Çaylı, Sevil; Şimşek, Gülçin; Gümüşderelioğlu, Menemşe
ABSTRACT: Purpose : Choukroun's platelet-rich fibrin (PRF), a second-generation platelet concentrate, has unique morphological and chemical features and may be considered as a scaffold for scleral reinforcement and regeneration. The purpose of this study was to compare the use of xenogenic human-derived amniotic membrane (HAM), allogenic sclera, and autogenic PRF in rabbit lamellar scleral defect model with respect to both anatomical and immunohistochemical improvement. Methods : A total of 45 adult New Zealand rabbits were randomized into five groups: normal control; without surgical procedure, negative control; scleral defect model (SDM), xenogenic HAM; SDM+HAM graft, allogenic sclera; SDM+allogenic sclera graft, autogenic PRF; SDM+autogenic PRF graft. Clinical findings, Hematoxylin&Eozin (HE), Masson Trichrome, Verhoeff Acid Fuchsin, Transforming Growth Factor β Receptor 1, Fibroblast Growth Factor, Bone Morphogenetic Protein 2, collagen type 1, aggrecan, and Matrix Metalloproteinase 2 were evaluated. Results : Ocular surface inflammation was significantly lower in normal control and autogenic PRF groups ( p < .001). Graft was avascular and not integrated to scleral wound area in 25% rabbits of allogenic sclera group ( p = .02), was out of the scleral wound in 33.3% rabbits of xenogenic HAM group ( p > .05), all the grafts were at the normal location and viable in autogenic PRF group. The inflammation and vascularization in autogenic PRF group was significantly lower than negative control and xenogenic HAM groups in HE ( p < .001). The collagen score of negative control and xenogenic HAM groups were significantly lower than normal control ( p < .001) and autogenic PRF ( p < .001) groups. There were insignificant differences between allogenic sclera and autogenic PRF groups ( p > .05). For immunohistochemistry, the closest values to normal control group were detected in autogenic PRF group for all immunomarkers. Conclusion : Autogenic PRF showed superior features via its excellent anatomical and chemical composition for scleral regeneration when compared to single-layered xenogenic HAM and allogenic sclera grafts.